Draft Annual Plan 1983-84 Volume XI Hill Areas Government of Assam - Planning Commission (Planning Commission, 1983)
Two District hospitals, two District T.B. Centres, one District Health Education Bureau and two District Medical Stores were in position. Three Leprosy Control Units. 19 Survey Education and Treatment Centres and one Temporary Hospitalisation Ward (20 beds) under Leprosy Control Programme were functioning in the area.
Office of the Development Commissioner for the Hill Areas of Assam